The Paradoxical Response in an Immunocompromised Patient With Disseminated Mycobacterium chelonae Infection. Issue 2 (March 2020) - Modi, Anita; Bravo, Tricia
Abstract : Abstract: The paradoxical response, a form of immune reconstitution inflammatory syndrome, merits immunosuppression in addition to antimycobacterial therapy in patients with nontuberculous mycobacterial (NTM) infections. Well-described in Mycobacterium tuberculosis infections, the paradoxical response in NTM infections is less defined. We share an immunocompromised host with disseminated NTM and the paradoxical response. Abstract : The paradoxical response, a form of immune reconstitution inflammatory syndrome, merits immunosuppression in addition to antimycobacterial therapy in patients with nontuberculous mycobacterial (NTM) infections. Well-describe in Mycobacterium tuberculosis infections, the paradoxical response in NTM infections is less defi ned. The authors share an immunocompromised host with disseminated NTM and the paradoxical response that manifested with clinical worsening despite appropriate antimycobacterial therapy and improved with steroids.